Augmented Reality-Based Learning Media as an Innovative Approach to Enhance Students’ Conceptual Comprehension and Creativity - Rahmi Oktarina; Yuni Mala Sari; Vici Syahril Chairani; Tyas Asih Surya Mentari; Rima Agustia Utami (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Low conceptual understanding and limited creativity remain persistent issues in Beauty and Cosmetology Education, primarily due to lecturer-centered instruction and the absence of interactive visual learning media. This study investigates the effect of Augmented Reality (AR)-based learning media on students’ conceptual understanding and creative thinking. A quasi-experimental design with a non-equivalent control group was employed involving 32 students divided into experimental and control groups. The experimental group was exposed to AR-integrated instruction, while the control group received conventional teaching. Data were collected using essay-based assessments measuring conceptual understanding and creative thinking across the dimensions of productivity, adaptability, novelty, and elaboration. Inferential statistical analysis was applied to test mean differences between groups. Results indicate that the experimental group significantly outperformed the control group (p < 0.05) in both conceptual understanding and creativity measures. These findings demonstrate that AR-based instructional media enhances cognitive processing and supports higher-order thinking through immersive visualization and contextualized learning experiences. Accordingly, AR integration offers a viable pedagogical approach for improving learning outcomes in cosmetology education, particularly in fostering conceptual mastery and creative competence